Supramolecular self-assembly of triazine-based small molecules: targeting the endoplasmic reticulum in cancer cells. Issue 7 (6th February 2019) - Ghosh, Chandramouli; Nandi, Aditi; Basu, Sudipta
Abstract : We developed supramolecular self-assembled nanoparticles for targeting the endoplasmic reticulum (ER) in cancer cells. Abstract : The endoplasmic reticulum (ER) is one of the most important organelles controlling myriads of cellular functions including protein folding/misfolding/unfolding, calcium ion homeostasis and lipid biosynthesis. Subsequently, due to its functional dysregulation in cancer cells, it has emerged as an interesting target for anti-cancer therapy. However, specific targeting of the ER in cancer cells remains a major challenge due to the lack of ER-selective chemical tools. Furthermore, for performing multiple cellular functions the ER is dependent on the nucleus through complicated cross-talk. Herein, we have engineered a supramolecular self-assembled hexameric rosette structure from two small molecules: tri-substituted triazine and 5-fluorouracil (5-FU). This rosette structure consists of an ER-targeting moiety with a fluorescence tag, an ER-stress inducer and a nuclear DNA damaging drug simultaneously, which further self-assembled into an ER-targeting spherical nano-scale particle (ER-NP). These ER-NPs internalized into HeLa cervical cancer cells by macropinocytosis and specifically localized into the ER to induce ER stress and DNA damage leading to cell death through apoptosis. Interestingly, ER-NPs initiated autophagy, inhibited by a combination of ER-NPs and chloroquine (CQ) to augment cancer cell death. This work has the potential to exploit the concept of supramolecular self-assembly into developing novel nano-scale materials for specific sub-cellular targeting of multiple organelles for future anti-cancer therapy.